Maternal hypothyroidism and neonatal outcome - R., Shravani M.; D., Tharashree C.; T., Yashodha H. (International Journal of Contemporary Pediatrics, 2018)
Background: Hypothyroidism is widely prevalent in pregnant women and the rate of detection, especially in a developing country like India, has not kept pace with the magnitude of the problem. The present study was conducted to evaluate thyroid function in neonates born to mothers with hypothyroidism. Methods: A prospective observational study was conducted in KIMS Hospital Tertiary care center for 6 months. A total of 106 neonates born to mothers with hypothyroidism were included in the study. Thyroid functions of these babies were assessed at 72 hours of life. Results: In present study, 11.8 % of mothers were hypothyroid of which 87 % were subclinical hypothyroidism and 13 % of overt hypothyroidism due to adaptation of universal screening rather than targeted screening for hypothyroidism which would otherwise go unrecognised and untreated. Conclusions: All the babies had normal TSH and T4 levels which was probably due to early diagnosis and timely initiation of treatment to the mothers with hypothyroidism.